Pengaruh NIM dan BOPO Terhadap Perubahan Laba - Minar Sumanullang; Herlina Littu; Siti Nuridah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Manufacturing companies play an important role in a country's economy, especially in increasing national income. However, a number of external and internal factors can influence a company's financial performance. Some of them are Net Interest Margin (NIM) and Operating Costs to Income Ratio (BOPO), which can influence the company's profit change practices. This research aims to analyze the influence of NIM and BOPO on profit change practices in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2020-2022 period. Net Interest Margin (NIM) and Operational Costs to Income Ratio (BOPO) are indicators and analytical tools. Changes in NIM or BOPO do not always have the same direct impact on changes in profits, but both can provide important information that can help bank management. In this research we used financial data from manufacturing companies listed on the IDX for a three year period, namely 2020, 2021 and 2022. The sample used in this research was 132 samples with a total of 44 companies. The sample was selected using purposive sampling technique. This research uses a multiple regression analysis method using a sample of manufacturing companies listed on the IDX. The data used was obtained from company financial reports published on the official IDX website. Based on the results of the partial t test, it can be seen if the significance value of NIM is 0.00 < 0.05. Meanwhile, the significance value of the BOPO variable is 0.593 > 0.05. The second hypothesis is accepted as the same meaning if the NIM and BOPO variables have a significant effect on the ROA variable. The results of this research show that NIM and BOPO have a significant effect on changes in profits in manufacturing companies listed on the IDX. Therefore, manufacturing companies are expected to pay attention to the performance of NIM and BOPO in making financial decisions and business strategies.